Organizational structure of the Mangalarga herd and the influence of geographic distribution and different coats on the genetic diversity - Andreza Correia da Silva; Juliano Martins Santiago; Jorge Eduardo Cavalcante Lucena; Caline Angélica de Menezes Sá Nascimento; Janaina Kelli Gomes Arandas; Laura Leandro da Rocha; Ana Paula Gomes Pinto (Revista Brasileira de Zootecnia)
ABSTRACT The objective was to describe the organizational structure of the Mangalarga herd and evaluate the influence of geographic distribution and different coats on the population structure and genetic diversity. Genealogic data of horses born between 1919 and 2018 were submitted to the software ENDOG 4.8, corresponding to the total population (TP), and those born between 2009 and 2018, representing the reference population (RP). Wright’s fixation index, inbreeding coefficient (F), and average relatedness (AR) were estimated considering each Brazilian state as a subpopulation and, afterwards, the different coat colors as subpopulations. The origin and use of breeding animals were used as parameters to classify the populations in the different states within the strata: Nucleus, Multiplier, Commercial, and Isolated. Considering Brazilian states as subpopulations, the mean value estimated for FIS in the RP was 0.0091, FIT of 0.0107, FST of 0.0016, F of 5.81%, and AR of 3.81%. In the RP, the sorrel coat accounted for 87.58% of the genetic contribution. Considering different coat colors as subpopulations, the mean value estimated for FIS in the RP was 0.0103, FIT of 0.0107, FST of 0.0004, F of 3.53%, and AR of 3.29%. In the RP, the breed is present in 14 states. Of those, 53.33% were classified as Multiplier herds and 46.67% as Commercial herds. The organizational structure of the Mangalarga breed is not pyramid shaped and, even with the greater genetic contribution of the state of São Paulo and of the sorrel coat, the inbreeding coefficient is under control.